Foot and mouth disease (FMD)-1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Dr Ndabezinhle Mkhwananzi, Veterinary officer in Matabeleland North province Zimbabwe.